Investigating the impact of tourism on gross regional domestic product growth in Batu City - Adiarti, Yuanita Soca; Wijaya, Riko Setya (Journal of Business Management and Economic Development, 2024)
Batu City is a tourism city that has great potential in East Java Province. However, based on existing data, the Gross Regional Domestic Product of Batu City's tourism sector in 2020 has decreased significantly compared to other cities in East Java. This research aims to examine the influence of the number of tourist attractions, number of tourists, number of hotels, and number of restaurants on Gross Regional Domestic Product in Batu City. This research uses secondary data in the form of a time series covering 12 years, from 2011 to 2022. Data analysis was carried out using the multiple linear regression method using SPSS 27 software. Based on the results of the analysis, overall, the independent variables such as the number of tourist attractions, number of tourists, number of hotels, and number of restaurants have a positive influence on GRDP. However, partially the number of tourist attractions, the number of tourists, and the number of restaurants have an insignificant positive influence on GRDP, while the number of hotels has a positive and significant influence on GRDP in Batu City.